Strategic Stability: Dynamics and Factors of Transformation - K. V. Bogdanov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper provides a comparative analysis study of the dynamics and mechanisms of the strategic stability transformation both during the Cold War and at present. Drawing on the analysis of the factors affecting strategic stability in different time periods, the author outlines the priorities of this transformation. Its basic principles are confined to the stability of nuclear deterrence in any realistic scenarios and do not provide for practical action. Hence, one should distinguish them from applied solutions for calculating military-strategic balances and elaboration of arms control agreements. The latter depend on the current strategic landscape subject to constant, sometimes drastic change, as both the Cold War history and the recent developments testify. The choice of particular type of representation of strategic stability is determined by the nature of the most dangerous ongoing trends, and relies on a set of three basic groups of factors (political-military, military-technical, and military-strategic) existing at a given time. This necessitates constant revaluation of these factors and development of new practical measures to build up nuclear deterrence.The paper assesses the current set of relevant factors affecting stability of nuclear deterrence, and then compares it with the commonly used model of strategic stability based on the logic of arms control negotiations of the late 1980s. The author highlights the limitations of the latter model applicability to the present strategic landscape, and outlines the key factors that erode the current understanding of strategic stability (as it was stipulated in the 1990 U.S.–Soviet Joint Statement). In particular the author emphasizes the increasing complexity of international landscape as compared to the Cold War period: new and unanticipated challenges have affected all three above-mentioned groups of factors. The paper ends up with the analysis of the possible developments in the field of arms control that could alleviate tensions and increase strategic stability.